Silencing of lncRNA UCA1 inhibited the pathological progression in PCOS mice through the regulation of PI3K/AKT signaling pathway - Dongyong Yang; Yanqing Wang; Yajing Zheng; Fangfang Dai; Shiyi Liu; Mengqin Yuan; Zhimin Deng; Anyu Bao; Yanxiang Cheng (BMC, 2021)
Abstract Background Polycystic ovary syndrome (PCOS) is the most common hormonal disorder among reproductive-aged women worldwide, however, the mechanisms and progression of PCOS still unclear due to its heterogeneous nature. Using the human granulosa-like tumor cell line (KGN) and PCOS mice model, we explored the function of lncRNA UCA1 in the pathological progression of PCOS. Results CCK8 assay and Flow cytometry were used to do the cell cycle, apoptosis and proliferation analysis, the results showed that UCA1 knockdown in KGN cells inhibited cell proliferation by blocking cell cycle progression and promoted cell apoptosis. In the in vivo experiment, the ovary of PCOS mice was injected with lentivirus carrying sh-UCA1, the results showed that knockdown of lncRNA UCA1 attenuated the ovary structural damage, increased the number of granular cells, inhibited serum insulin and testosterone release, and reduced the pro-inflammatory cytokine production. Western blot also revealed that UCA1 knockdown in PCOS mice repressed AKT activation, inhibitor experiment demonstrated that suppression of AKT signaling pathway, inhibited the cell proliferation and promoted apoptosis. Conclusions Our study revealed that, in vitro, UCA1 knockdown influenced the apoptosis and proliferation of KGN cells, in vivo, silencing of UCA1 regulated the ovary structural damage, serum insulin release, pro-inflammatory production, and AKT signaling pathway activation, suggesting lncRNA UCA1 plays an important role in the pathological progression of PCOS.